Presenting an algorithm of integer nonlinear multiple objective programming in conditions of uncertainty for balanced scorecard method (case study in Islamic Azad University, Semnan Branch) - Hamedi, Mohammad; Karkehabadi, Hamidreza (Management science letters, 2012)
Balanced scorecard is a performance appraisal method planned for measuring the organizational efficiency to develop their strategies. Organization’s strategies in a specified period are the main inputs in this model. Furthermore, due to nature, experts' opinions play the vital role in determining the strategies. In this research, the proposed algorithm is designed by using fuzzy set covering problem and non-linear multiple objective integer programming (zero and one variables), so that it can be useful to choose the best combination of strategies for specified period of time with the least deviation in experts` opinions. The presented model is carried out in Islamic Azad University, Semnan Branch. The results indicate that the designed model can provide the best combination of strategies for entering into the balanced scorecard system.